2013
DOI: 10.2119/molmed.2012.00352
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor (MIF) and Thyroid Hormone Alterations in Antineutrophil Cytoplasmic Antibody (ANCA)-Associated Vasculitis (AAV)

Abstract: Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine known to be released from lymphocytes, macrophages and endothelial cells and also in animal models shown to be inducible with glucocorticoids (GC). In contrast, thyroxine seems to antagonize MIF activity. To investigate whether MIF is increased in active antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and possible correlations with GC dosing and thyroid hormone levels, 27 consecutive patients with active AAV were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…These findings mirror the associations that have been reported previously between MIF polymorphisms and disease susceptibility or clinical severity in several autoimmune diseases, including systemic lupus erythematosus (13, 41), scleroderma (14), rheumatoid arthritis (15, 42), autoimmune liver disease (43), and celiac disease (44), as well as in granulomatous conditions such as sarcoidosis (6) and tuberculosis (25, 45). Furthermore, higher MIF plasma levels were noted in patients with GPA when compared to healthy controls, a finding previously reported in ANCA-associated vasculitis and other granulomatous diseases (8, 46, 47). Recent genome-wide association studies have identified several gene polymorphisms that are associated with susceptibility to GPA.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings mirror the associations that have been reported previously between MIF polymorphisms and disease susceptibility or clinical severity in several autoimmune diseases, including systemic lupus erythematosus (13, 41), scleroderma (14), rheumatoid arthritis (15, 42), autoimmune liver disease (43), and celiac disease (44), as well as in granulomatous conditions such as sarcoidosis (6) and tuberculosis (25, 45). Furthermore, higher MIF plasma levels were noted in patients with GPA when compared to healthy controls, a finding previously reported in ANCA-associated vasculitis and other granulomatous diseases (8, 46, 47). Recent genome-wide association studies have identified several gene polymorphisms that are associated with susceptibility to GPA.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, higher MIF plasma levels were noted in patients with GPA compared to healthy controls, a finding previously reported in AAV and other granulomatous diseases . Recent genome‐wide association studies have identified several gene polymorphisms that are associated with susceptibility to GPA.…”
Section: Discussionsupporting
confidence: 69%
“…In patients with severe sepsis, low plasma T4 concentrations were inversely correlated with plasma MIF concentrations ( 65 ). In our human study, there was a strong correlation over time between the baseline MIF/T4 ratio and the MIF/T4 ratio at 6 months in AAV patients in remission ( 61 ). Both the preclinical and clinical data therefore suggest that blocking the inflammatory active site of MIF may both reduce inflammatory responses and improve the availability of T4.…”
Section: Mif and Vasculitismentioning
confidence: 71%
“…We studied MIF in a prospective study of incident AAV patients at induction treatment, and at follow-up at 3 and 6 months and found elevated plasma levels at baseline. MIF decreased significantly during follow-up when most patients were in remission, but remained still elevated as compared with controls at all time points ( 61 ). MIF levels did not correlate with CRP, creatinine, or organ involvement.…”
Section: Mif and Vasculitismentioning
confidence: 99%
“…T4 is considered as a potential antagonist of MIF as the binding of T4 suppresses the catalytic activity of the hydrophobic pocket that is associated with the pro-inflammatory activities of MIF. In patients with active antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), an increase in MIF was detected with a decreased fT3 level [46]. It is noteworthy that MIF binds to its natural receptor CD74, a type II transmembrane protein, to initiate downstream inflammatory signals.…”
Section: Discussionmentioning
confidence: 99%